Pengaruh Strategi Promosi, Ulasan Elektronik, dan Kualitas Produk terhadap Keputusan Pembelian Konsumen - Riyono; Nuri Wulandari; Hesti Ristanto (Jurnal Bingkai Ekonomi (JBE), 2025)
This research seeks to explore the impact of marketing tactics, Electronic Word of Mouth (E-WoM), and product excellence on consumer buying intentions at PT Fentura Windows Asia Semarang. A quantitative methodology was implemented, involving over 96 participants chosen through purposeful and incidental sampling methods. Data was gathered using a closed-ended survey featuring a 5-point Likert scale and analyzed via multiple linear regression to assess the influence of each independent variable on the dependent variable. The findings indicate that marketing tactics exert a positive yet insignificant effect on buying intentions, suggesting the necessity for more creative and effective promotional methods. Conversely, E-WoM and product excellence demonstrate positive and significant impacts on consumer buying intentions, underscoring the crucial role of online reviews and product perceptions in shaping purchasing choices. Collectively, these three elements account for 32.1% of buying intentions, leaving a substantial 67.9% influenced by additional factors not covered in this study. In light of these results, the research advocates for companies to refine digital marketing strategies, improve product quality, and strategically manage E-WoM through customer reviews on digital platforms. The practical implications emphasize the importance of a cohesive strategy integrating marketing tactics, E-WoM, and product excellence to enhance competitiveness and cultivate lasting customer loyalty.